Ropivacaine 0.025% mixed with fentanyl 3.0 μg/ml and epinephrine 0.5 μg/ml is effective for epidural patient-controlled analgesia after cesarean section - Shaul Cohen; Renu Chhokra; Mark H Stein; John T Denny; Shruti Shah; Adil Mohiuddin; Rotem Naftalovich; Rong Zhao; Anna Pashkova; Noah Rolleri; Arpan G Patel; Christine W Hunter-Fratzola (Wolters Kluwer Medknow Publications, 2015)
Background and Aims: We aimed to determine the ropivacaine concentration that provided adequate analgesia with early ambulation and minimal urinary retention or other side-effects when used with fentanyl and epinephrine for patient-controlled epidural analgesia (PCEA) after elective cesarean section. Material and Methods: Forty-eight patients were randomized to four groups in a double-blinded fashion. All groups received an initial 10 ml/h of epidural study solution for 24 h. The solution contained: 0.2, 0.1, 0.05, or 0.025% ropivacaine for Groups I-IV, respectively, with fentanyl 3.0 μg/ml and epinephrine 0.5 μg/ml. Patients could administer additional PCEA doses of 4 ml of their study solution with a lock-out time of 10 min. Overall satisfaction, side-effects, motor block, neurologic function, and pain using Visual Analog Scale were assessed. Results: Patients in all groups showed no difference in sedation, pruritus, nausea, vomiting, and uterine cramps. Pain scores at rest were lower for Group IV than Groups I-III (P < 0.001). Twelve, five, one, and zero patients could not ambulate in Groups I-IV, respectively. Nine, nine, two, and zero (III <I and II, P = 0.02; IV P = 0.001) patients reported urinary retention in Groups I-IV, respectively. Overall satisfaction scores were high for all groups. Neonatal behavior score was similar and high in all groups. Conclusion: 0.025% ropivacaine PCEA combined with fentanyl and epinephrine provided effective pain relief after cesarean section with early ambulation and without sensory loss, urinary retention, or increase of side-effects.